Imagining the unimaginable : World War, modern art, & the politics of public culture in Russia, 1914-1917 - Cohen, Aaron J. (Studies in war, society, and the military., 2008)
Imagining the Unimaginable deftly reveals the experiences of artists and developments in mass culture and in the press against the backdrop of the broader trends in Russian politics, economics, and social life from the mid-nineteenth century to the revolution. After 1914, avant-garde artists began to imagine many things that had once seemed unimaginable. As Marc Chagall later remarked,?The war was another plastic work that totally absorbed us, which reformed our forms, destroyed the lines, and gave a new look to the universe.?